Advanced swing trading : strategies to predict, identify, and trade future market swings - Crane, John. (Hoboken, N.J. : Wiley, 2003)
The book discusses and illustrates a whole new way of using time, price, and patterns to predict, identify, and trade future market swings.
Series statement on jacket.
Includes index.
rua 30/09/14
Loans
Keywords: Investment analysis; Portfolio management; Stocks